2007
DOI: 10.1348/135910706x96896
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiff dental study: A 20‐year critical evaluation of the psychological health gain from orthodontic treatment

Abstract: Longitudinal analysis revealed that the observed effect of orthodontic treatment on self esteem at outcome was accounted for by self esteem at baseline. Prior need for treatment assessed in childhood made a small contribution to the prediction of self-esteem 20 years later in adulthood. Dental status in adulthood, whilst statistically significant, appeared to be of minor importance in a model that included other psychological variables. When prior need for treatment was taken into account there was little obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 50 publications
6
48
0
2
Order By: Relevance
“…One randomised controlled trial did find a short term improvement in self-concept when children with a class II division 1 malocclusion were treated early (aged 8 to 10) compared with an untreated control; 30 however other studies have found that orthodontic treatment has no effect on the psychological well-being of individuals, and self-esteem in particular, over the long term. [31][32][33] This has not been a surprising finding to others either. 34 Pitner cites the work of Diener and colleagues, who have studied the ability of people to adapt over time to new situations and extreme life events.…”
Section: Psychological Well-beingmentioning
confidence: 54%
“…One randomised controlled trial did find a short term improvement in self-concept when children with a class II division 1 malocclusion were treated early (aged 8 to 10) compared with an untreated control; 30 however other studies have found that orthodontic treatment has no effect on the psychological well-being of individuals, and self-esteem in particular, over the long term. [31][32][33] This has not been a surprising finding to others either. 34 Pitner cites the work of Diener and colleagues, who have studied the ability of people to adapt over time to new situations and extreme life events.…”
Section: Psychological Well-beingmentioning
confidence: 54%
“…[36][37][38] The impact of oral health conditions on quality of life, especially in items of satisfaction with appearance, may result in feelings of shame in social contacts and those who are psychosocially disadvantaged. 10,15,17,24,30,38,39 Therefore, the expected benefits of orthodontic treatment would include an enhancement of self-esteem and a reduction in social anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent 20-year longitudinal study concluded that there was little objective evidence to support the assumption that orthodontics improves long-term psychological health. Thus, orthodontics cannot be justified on psychological grounds alone [33]. Therefore, further studies are needed to provide a greater understanding of the consequences of malocclusion, the effects of malocclusion if left untreated, and also the possible benefits of orthodontic care on day-to-day activities.…”
Section: Discussionmentioning
confidence: 99%